Electrolytic capacitor and manufacturing method

By forming a pseudo-boehmite layer in an electrolytic capacitor and controlling the boric acid content, the problems of metal exposure and hydrogen generation of the conduction guide tile in a high temperature environment are solved, and the long life and high stability of the electrolytic capacitor are achieved.

JP2025059293APending Publication Date: 2025-04-10NIPPON CHEMI CON CORP
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2023169297
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-09-29
Publication Date
2025-04-10

AI Technical Summary

Technical Problem

In electrolytic capacitors for high voltage applications, when used for a long time in high temperature environments, the degradation of the oxide film leads to exposure of the guide tile metal, generating hydrogen, and shortening the capacitor life.

Method used

The pseudo-boehmite layer and an electrolyte containing 9 wt% or less boric acid were used in an electrolytic capacitor, and a glycerol-based solvent was used during the manufacturing process to control the thickness of the pseudo-boehmite layer and the content of boric acid to inhibit the degradation of the oxide film and the formation of hydrogen.

Benefits of technology

It effectively suppresses the generation of hydrogen in high-temperature environments, extends the service life of the electrolytic capacitor, and improves its stability in high-voltage applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025059293000001_ABST
    Figure 2025059293000001_ABST
Patent Text Reader

Abstract

To provide an electrolytic capacitor that suppresses hydrogen gas generation in high pressure applications and has a long life, and to provide a manufacturing method for such an electrolytic capacitor.SOLUTION: An electrolytic capacitor includes an anode foil made of a valve metal, a cathode body, and an electrolyte. The anode foil has a dielectric film formed on the surface of the anode foil, and a pseudo-boehmite layer formed on the dielectric film and having a density of 1.0 mg / cm2 or more. The electrolyte contains boric acid in an amount of 9 wt% or less with respect to the total amount of the electrolyte. The manufacturing method includes a pre-chemical conversion step, a chemical conversion step, an element forming step, and an impregnation step. The pre-chemical conversion step forms a pseudo-boehmite layer on an anode foil having a valve metal as a base material. The chemical conversion step forms a dielectric film while leaving the pseudo-boehmite layer. The element forming step forms a capacitor element in which the anode foil and the cathode body face each other via a separator. The impregnation step impregnates the capacitor element with an electrolyte having a boric acid concentration of 9 wt% or less.SELECTED DRAWING: Figure 4
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an electrolytic capacitor and a method for manufacturing the same. [Background technology]

[0002] An electrolytic capacitor has an anode foil and a cathode body made of valve metal such as tantalum or aluminum. The anode foil is enlarged by forming the valve metal into a sintered or etched foil, etc., and has a dielectric coating layer on the enlarged surface. An electrolyte is interposed between the anode foil and the cathode body. The electrolyte is in close contact with the uneven surface of the anode foil and functions as a true cathode.

[0003] The cathode body of an electrolytic capacitor undergoes a dissolution reaction due to a hydration reaction, which generates hydrogen gas. That is, in the cathode body of an electrolytic capacitor, hydrogen gas is generated according to the following chemical reaction formula (1). It is believed that moisture gets mixed in during the manufacturing process of the electrolytic capacitor. TIFF2025059293000002.tif7163

[0004] Hydrogen gas increases the internal pressure of the electrolytic capacitor, which may cause the case housing the capacitor element to bulge, the sealing member sealing the capacitor element to bulge, or the pressure relief valve provided in the electrolytic capacitor to open.

[0005] Therefore, it has been known in the past to subject a cathode foil to an immersion treatment or chemical conversion treatment in an aqueous phosphoric acid solution, thereby coating the cathode body with an oxide film and protecting the valve metal constituting the cathode body from the electrolyte (see, for example, Patent Document 1). [Prior art documents] [Patent documents]

[0006] [Patent Document 1] Patent Publication No. 2010-219083 Summary of the Invention [Problem to be solved by the invention]

[0007] However, the inventors have found through experiments that, in electrolytic capacitors for high voltage applications, for example rated at 550V or more, when exposed to a high temperature environment for a long period of time, even if an oxide film is formed on the cathode body, the valve metal of the cathode body is exposed due to hydration deterioration of this oxide film. Because the oxide film on the cathode body is thin, the cathode body's base metal is particularly prone to exposure. In other words, when an electrolytic capacitor for high voltage applications is exposed to a high temperature environment for a long period of time, the following chemical reaction formula (2) occurs in the cathode body. TIFF2025059293000003.tif7163

[0008] In this case, even if the cathode body is protected by an oxide film, the deterioration of the oxide film causes a dissolution reaction of the valve metal that constitutes the cathode body, generating hydrogen gas and shortening the life of the electrolytic capacitor.

[0009] The present invention has been proposed to solve the above problems, and an object of the present invention is to provide an electrolytic capacitor that suppresses hydrogen gas generation in high-pressure applications and has a long life, and a manufacturing method thereof. [Means for solving the problem]

[0010] In order to achieve the above object, the electrolytic capacitor of the present embodiment is an electrolytic capacitor including an anode foil made of a valve metal, a cathode body, and an electrolyte, the anode foil including a dielectric film formed on a surface layer of the anode foil, and a dielectric film having a concentration of 1.0 mg / cm formed on the dielectric film. 2 The electrolytic solution has the above pseudo-boehmite layer, and the electrolytic solution contains boric acid in an amount of 9 wt % or less with respect to the total amount of the electrolytic solution.

[0011] The electrolyte may contain a solvent of a glycol compound.

[0012] The weight of the pseudo-boehmite layer is 1.3 mg / cm 2 The above may be adopted.

[0013] The boric acid may be contained in an amount of 8.3 wt % or less based on the total amount of the electrolyte.

[0014] The electrolytic solution may contain mannitol, and a weight ratio of the boric acid (A) to the mannitol (B) in the electrolytic solution may be A:B=1:0.7 or more.

[0015] In order to achieve the above object, the method for producing an electrolytic capacitor according to the present embodiment includes a pre-chemical conversion step of forming a pseudo-boehmite layer on an anode foil having a valve metal as a base material, and a step of depositing the pseudo-boehmite layer at a concentration of 1.0 mg / cm. 2 The method includes a chemical conversion step of forming the dielectric film while leaving the above, an element formation step of forming a capacitor element in which the anode foil that has been subjected to the chemical conversion step and the cathode body are opposed to each other with a separator interposed therebetween, and an impregnation step of impregnating the capacitor element with an electrolyte solution having a boric acid concentration of 9 wt % or less. Effect of the Invention

[0016] According to the present invention, the generation of hydrogen gas is suppressed, and the life of the electrolytic capacitor is extended. [Brief description of the drawings]

[0017] [Figure 1] 13 is a graph showing the transition of potential from a steady state to 5 minutes after the start of measurement. [Diagram 2] 13 is a graph showing the transition of potential from a steady state to 5 minutes after the start of measurement. [Diagram 3] 1 is a graph showing the relationship between the potential and the weight of the pseudo-boehmite layer when an electrolyte solution having a boric acid concentration of 11 wt % is used. [Figure 4] 1 is a graph showing the relationship between boric acid concentration and the potential of a cathode foil. [Diagram 5] 1 is a graph showing the relationship between the weight ratio of mannitol to boric acid and the potential of a cathode foil. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0018] DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS An electrolytic capacitor and a manufacturing method thereof according to an embodiment of the present invention will be described below. Note that the present invention is not limited to the embodiment described below.

[0019] (Electrolytic capacitor) An electrolytic capacitor includes a capacitor element. The capacitor element includes an anode body made of a valve metal, a cathode body made of a valve metal, and an electrolyte. A dielectric film is formed on the surface of the anode body. An oxide film is also formed on the surface of the cathode body. The anode body and the cathode body face each other with a separator in between. The electrolyte is impregnated into the anode body and the separator, and is interposed between the dielectric film of the anode body and the cathode body, and is in close contact with the dielectric film of the anode body to function as a true cathode.

[0020] This capacitor element is a wound type. In a wound type, the anode body and the cathode body are wound with a separator sandwiched between them. An anode lead is connected to the anode body, and a cathode lead is connected to the cathode body, and these are drawn out from the end faces of the capacitor element. The electrolytic capacitor is electrically connected to the mounting circuit via the anode lead and the cathode lead. By being conductive to the mounting circuit, the electrolytic capacitor becomes a passive element that obtains capacitance due to the dielectric polarization action of the dielectric film and stores and discharges electric charge.

[0021] A pseudo-boehmite layer is further formed on the dielectric film of the anode body. When the valve metal is aluminum, the pseudo-boehmite layer contains hydrated oxide of aluminum, which is AlOOH·xH2O or Al2O3·xH2O. The dielectric film is an aluminum oxide layer containing γ-alumina, which is a crystalline oxide. This pseudo-boehmite layer is dense inside and functions as a resistive layer to improve the withstand voltage of the electrolytic capacitor.

[0022] The electrolyte contains boric acid as a solute. It has been confirmed that when the pseudo-boehmite layer and boric acid are present, the cathode body dissolves and generates hydrogen gas, shortening the life of the electrolytic capacitor, even if moisture contamination is strictly controlled during the manufacturing process. Although this is speculation and not limited to this, it is believed that moisture is generated by a dehydration reaction between the pseudo-boehmite layer of the anode body and boric acid, as shown in the chemical reaction formula (3) below. (C3) TIFF2025059293000004.tif25164

[0023] This moisture removes the oxide film as shown in chemical reaction formula (2). When the bare valve metal of the cathode body is exposed, a dissolution reaction of the valve metal occurs through a hydration reaction as shown in chemical reaction formula (3). It is believed that this dissolution reaction produces hydrogen gas.

[0024] However, the weight of the pseudo-boehmite layer is 1.37 mg / cm 2 The content of boric acid is set to 9 wt% or less based on the total amount of the electrolyte. In this case, removal of the oxide film on the cathode body is suppressed. Therefore, generation of hydrogen gas in the electrolytic capacitor is suppressed, and the life of the electrolytic capacitor is improved. The weight of the pseudo-boehmite layer is 1.0 mg / cm 2 The weight of the pseudo-boehmite layer is 2.5 mg / cm. 2 Less than 1.3 mg / cm 2 The content of boric acid may be 8.3 wt% or more based on the total amount of the electrolyte. If the content is 8.3 wt% or less, deterioration of the cathode body is further suppressed. In addition, from the viewpoint of suppressing an increase in ESR during use of the electrolytic capacitor, the content of boric acid is preferably 7.5 wt% or more.

[0025] (Anode body) Here, the valve metal of the anode body is aluminum, tantalum, niobium, niobium oxide, titanium, hafnium, zirconium, zinc, tungsten, bismuth, antimony, etc. The purity of the valve metal is preferably 99.9% or more for the anode foil, and other elements such as silicon, iron, copper, manganese, magnesium, chromium, zinc, titanium, vanadium, gallium, nickel, boron, and zirconium may be contained. The anode body is, for example, a foil body, and is formed by stretching the valve metal, etc. The anode body may be formed by sintering a powder of the valve metal.

[0026] The anode body has a surface-expanding layer formed on one or both sides thereof. The surface-expanding layer may be an etching layer formed by etching a foil, a sintered layer formed by sintering valve metal powder, or a vapor-deposited layer formed by vapor-depositing valve metal particles onto a foil. That is, the surface-expanding layer has a porous structure, consisting of tunnel-like pits, spongy pits, or voids between densely packed powder or particles.

[0027] The tunnel-shaped etching pit is a hole dug in the foil thickness direction. This tunnel-shaped etching pit is typically formed by passing a direct current in an acidic aqueous solution containing halogen ions such as hydrochloric acid. The tunnel-shaped etching pit is further enlarged by passing a direct current in an acidic aqueous solution such as nitric acid. The spongy etching pit makes the surface-enlarged layer into a sponge-like layer with fine voids extending in a space. This spongy etching pit is formed by passing an alternating current in an acidic aqueous solution containing halogen ions such as hydrochloric acid.

[0028] The sintered layer is produced by obtaining a powder of a valve metal of the same or different type as the foil body by a pulverization method, an atomization method, a melt spinning method, a rotating disk method, a rotating electrode method, or the like, forming a paste with a binder or a solvent, applying it to the foil body, drying it, and heating and sintering it in a vacuum or a reducing atmosphere, or the like. The atomization method may be any of a water atomization method, a gas atomization method, and a water gas atomization method. The vapor deposition layer is produced by, for example, a resistance heating vapor deposition method or an electron beam heating vapor deposition method. This vapor deposition layer is formed by heating and evaporating a valve metal of the same or different type as the foil body by resistance heat or electron beam energy, and depositing the vapor of the valve metal particles on the surface of the foil body.

[0029] The pseudo-boehmite layer is formed by immersing the anode body in pure water at 80°C or higher or boiling water before forming the dielectric film. The immersion time may be determined according to the desired amount of the pseudo-boehmite layer and the balance between the withstand voltage and the electrostatic capacity. The initial weight of the pseudo-boehmite layer is proportional to the square root of the immersion time in the boiled pure water. Alternatively, the pseudo-boehmite layer may be dissolved from the surface by acid treatment such as immersion in phosphoric acid.

[0030] The dielectric film is typically an oxide film formed on the surface layer of the anode body. The dielectric film is formed by chemical conversion treatment. In the chemical conversion treatment, a voltage is applied to the anode body in a chemical conversion solution to achieve a desired withstand voltage. The chemical conversion solution is a solution free of halogen ions, such as a phosphoric acid-based chemical conversion solution such as ammonium dihydrogen phosphate, a boric acid-based chemical conversion solution such as ammonium borate, or an adipic acid-based chemical conversion solution such as ammonium adipate. In the chemical conversion treatment for forming the dielectric film, it is preferable to form a dielectric film having a thickness of 1.1 to 1.5 nm in order to obtain a withstand voltage of 1 V. For example, it is preferable to form a dielectric film having a thickness of at least 605 nm in order to obtain a withstand voltage of 550 V.

[0031] When a dielectric film is formed by applying a voltage of 300V or more, voids are generated in the dielectric film, so depolarization is preferably added. The depolarization repairs the voids in the dielectric film. The depolarization includes heat treatment, treatment with an acid solution, treatment with an alkaline solution, treatment with pure water, or a combination of these. In the heat treatment, for example, the anode body is exposed to a temperature environment of 450°C or more in the air to open isolated voids inside the dielectric film. In addition, for example, in the phosphoric acid solution treatment, the anode body is immersed in a phosphoric acid solution or an ammonium dihydrogen phosphate solution. This causes the dielectric film to stretch, the gas in the dielectric film to expand, or the layer of the dielectric film to be chemically dissolved, forming a path to the void and opening the void. This makes it easier for the re-chemical conversion solution to penetrate into the void, and the void can be repaired by performing the chemical conversion treatment again.

[0032] (cathode body) The purity of the valve metal of the cathode body is desirably 99% or more. A surface enlarged layer is formed on the cathode body, as with the anode body. A plain foil without a surface enlarged layer may be used as the cathode body. The cathode body forms a natural oxide film, or a thin oxide film of about 1 to 10 Vfs formed by chemical conversion treatment. The natural oxide film is formed by the cathode body reacting with oxygen in the air. The cathode body is, for example, a cathode foil, which is a foil body, and is formed by stretching a valve metal or the like.

[0033] (electrolyte) The electrolyte preferably contains mannite together with boric acid. The boric acid and mannite may form a complex compound. The boric acid and mannite are preferably such that the weight ratio B / A of the mannite to the boric acid in the electrolyte is 0.7 or more, where A is the weight of the boric acid and B is the weight of the mannite. When both boric acid and mannite are contained in this weight ratio, the oxide film formed on the cathode foil is prevented from dissolving in the electrolyte, even if the electrolytic capacitor is exposed to a high-temperature environment for a long period of time for high-voltage applications.

[0034] The electrolyte may contain other solutes than boric acid. Examples of organic acids that serve as anion components as other solutes include oxalic acid, succinic acid, glutaric acid, pimelic acid, suberic acid, sebacic acid, phthalic acid, isophthalic acid, terephthalic acid, maleic acid, adipic acid, benzoic acid, toluic acid, enanthic acid, malonic acid, 1,6-decanedicarboxylic acid, 1,7-octanedicarboxylic acid, azelaic acid, undecanediacid, dodecanediacid, tridecanediacid, t-butyladipic acid, and 11-vinyl-8-octadecenedioic acid, as well as carboxylic acids, phenols, and sulfonic acids. Examples of inorganic acids include phosphorous acid, hypophosphorous acid, carbonic acid, and silicic acid. Examples of composite compounds of organic and inorganic acids include borodisalicylic acid, borodioxalic acid, and borodiglycolic acid.

[0035] Examples of the cation include ammonium, quaternary ammonium, quaternary amidinium, amine, sodium, potassium, etc. Examples of the quaternary ammonium include tetramethylammonium, triethylmethylammonium, tetraethylammonium, etc. Examples of the quaternary amidinium include ethyldimethylimidazolinium, tetramethylimidazolinium, etc. Examples of the amine include primary amine, secondary amine, and tertiary amine. Examples of the primary amine include methylamine, ethylamine, and propylamine, and examples of the secondary amine include dimethylamine, diethylamine, ethylmethylamine, and dibutylamine, and examples of the tertiary amine include trimethylamine, triethylamine, tributylamine, ethyldimethylamine, and ethyldiisopropylamine.

[0036] The anions and cations may be added to the electrolytic solution in the form of ion-dissociable salts, or an acid that becomes an anion and a base that becomes a cation may be added to the electrolytic solution separately as solute components. The anions and cations may be used alone or in combination of two or more kinds.

[0037] The solvent may be either a protic polar solvent or an aprotic polar solvent. Representative examples of the protic polar solvent include monohydric alcohols, polyhydric alcohols, and oxyalcohol compounds. Representative examples of the aprotic polar solvent include sulfones, lactones, and cyclic amides.

[0038] Examples of monohydric alcohols include ethanol, propanol, butanol, pentanol, hexanol, cyclobutanol, cyclopentanol, cyclohexanol, benzyl alcohol, etc. Examples of polyhydric alcohols and oxyalcohol compounds include ethylene glycol, propylene glycol, glycerin, methyl cellosolve, ethyl cellosolve, methoxypropylene glycol, dimethoxypropanol, etc.

[0039] Examples of sulfones include dimethyl sulfone, ethyl methyl sulfone, diethyl sulfone, sulfolane, 3-methyl sulfolane, 2,4-dimethyl sulfolane, etc. Examples of lactones and cyclic amides include γ-butyrolactone, γ-valerolactone, δ-valerolactone, N-methyl-2-pyrrolidone, ethylene carbonate, propylene carbonate, butylene carbonate, isobutylene carbonate, etc.

[0040] As the solvent of the electrolytic solution, a glycol compound is preferred. The glycol compound is a compound having a structure in which hydrogen atoms bonded to two carbon atoms of an aliphatic hydrocarbon having two or more carbon atoms or a cyclic aliphatic hydrocarbon are replaced by hydroxyl groups one by one. The glycol compound has a high boiling point of 150°C or more. This glycol compound improves the chemical conversion property of the dielectric film, and can reduce the ESR of the electrolytic capacitor and improve the voltage resistance. Examples of the glycol compound include ethylene glycol, propylene glycol, diethylene glycol, triethylene glycol, and polyoxyethylene glycol. The electrolytic solution may contain one type of glycol compound solvent, or two or more types of glycol compound solvents. Furthermore, as the solvent, a glycol compound may be used alone, or a glycol compound may be combined with another type.

[0041] Furthermore, other additives can be added to the electrolyte. Examples of additives include phosphoric acid, phosphoric acid esters, and other phosphoric acid compounds, and nitro compounds. Nitro compounds suppress the generation of hydrogen gas in the electrolytic capacitor and are added as gas absorbents. Examples of nitro compounds include o-nitrobenzoic acid, m-nitrobenzoic acid, p-nitrobenzoic acid, o-nitrophenol, m-nitrophenol, and p-nitrophenol. Polymer components such as polyethylene glycol, polypropylene glycol, polyoxyethylene glycerin, silicone oil, polyvinyl alcohol, and colloidal silica can be added as additives that impart a pressure resistance improving effect.

[0042] (Separator) The separator is interposed between the anode foil and the cathode foil to prevent shorting between the anode foil and the cathode foil, and also holds the electrolyte. Examples of the separator include cellulose and mixed papers such as kraft, Manila hemp, esparto, hemp, and rayon, polyester-based resins such as polyethylene terephthalate, polybutylene terephthalate, polyethylene naphthalate, and derivatives thereof, polytetrafluoroethylene-based resins, polyvinylidene fluoride-based resins, vinylon-based resins, polyamide-based resins such as aliphatic polyamides, semi-aromatic polyamides, and fully aromatic polyamides, polyimide-based resins, polyethylene resins, polypropylene resins, trimethylpentene resins, polyphenylene sulfide resins, acrylic resins, and polyvinyl alcohol resins, and these resins can be used alone or in combination.

[0043] (Manufacturing method) An example of a manufacturing method for this electrolytic capacitor is as follows. First, the anode formation process includes a surface-expanding process, a pre-chemical conversion process, and a chemical conversion process. First, in the surface-expanding process, a surface-expanding layer is formed on one or both sides of the anode body. Next, in the pre-chemical conversion process, a pseudo-boehmite layer is formed on the surface layer along the irregularities of the surface-expanding layer of the anode body. Then, a chemical conversion process is performed to transform the pseudo-boehmite layer into a dielectric film from the boundary between the valve metal base metal of the anode body and the pseudo-boehmite layer toward the foil surface. In the cathode formation process, a surface enlargement layer is also formed on one or both sides of the cathode body as necessary, and an oxide film is formed on the surface. An anode lead and a cathode lead are electrically and mechanically connected to the anode body and the cathode body. The anode lead and the cathode lead are electrically and mechanically connected to the anode body and the cathode body by cold welding, ultrasonic welding, laser welding, or the like.

[0044] In the element formation process, long anode and cathode bodies are wound with a separator interposed therebetween to produce a cylindrical wound body. The separator is overlapped so that one end of the separator protrudes beyond one end of the anode and cathode bodies. The protruding separator is wound first so that the core of the wound body is aligned with the short sides of the anode and cathode bodies to produce a winding core. Then, the winding core is used as a winding axis to wind the long sides of the anode and cathode bodies by rolling them. The anode lead and the cathode lead are drawn out from the end faces of the capacitor element.

[0045] After the winding, a repair chemical conversion step may be provided to repair bare metal portions of the valve metal exposed when the anode body and the cathode body are cut to a desired width, and to repair defects in the anode body and the cathode body caused by physical stress such as winding.

[0046] In the repair anodization step, the wound body is immersed in anodization liquid and a voltage is applied. As the anodization liquid, a phosphoric acid-based anodization liquid such as ammonium dihydrogen phosphate, a boric acid-based anodization liquid such as ammonium borate, an adipic acid-based anodization liquid such as ammonium adipate, or an anodization liquid in which boric acid and a dicarboxylic acid such as citric acid are mixed is used. For example, the voltage is preferably set to a value of 0.1 to 1.2 times the anodization voltage. In addition, as a method of applying a voltage during repair anodization, a method of applying a constant voltage from the start of repair anodization, or a method of increasing the applied voltage stepwise at regular intervals, etc., are appropriately selected.

[0047] In the impregnation step, the capacitor element is immersed in an electrolyte containing boric acid, and the electrolyte is impregnated into the voids in the capacitor element. In order to impregnate the electrolyte into finer voids, a pressure reduction treatment or a pressure increase treatment may be performed as necessary. The electrolyte impregnation step may be repeated multiple times. For example, the inside of the capacitor element may be reduced in pressure, and the electrolyte may be injected into the inside of the capacitor element while pressurizing the electrolyte.

[0048] The capacitor element is housed in an exterior case that has one end closed and the other end open, and the capacitor element is sealed in the exterior case with a sealing body. The sealing body is a laminate of an elastic insulator such as a rubber plate or a hard substrate insulating plate such as a synthetic resin plate and an elastic insulator, which is crimped from the outside of the exterior case. A pressure valve is formed at the bottom of the case, which opens when the pressure inside the case exceeds a predetermined value. After the capacitor element is sealed in the exterior case, the electrolytic capacitor is subjected to an aging process to complete the production. In the aging process, a direct current voltage is applied to the electrolytic capacitor to repair defects in the dielectric oxide film layer and the like. EXAMPLES

[0049] (Example) The present invention will be described in more detail below with reference to examples, but the present invention is not limited to the following examples.

[0050] The electrolytic capacitors of Examples 1 to 12, Comparative Examples 1 to 4, and Reference Examples 1 to 8 were produced as follows. The cathode foil was a common strip-shaped aluminum foil. This cathode foil was subjected to an AC etching treatment to form a surface-expanding layer consisting of spongy etching pits on both sides of the foil. Next, the cathode foil was subjected to a chemical conversion treatment to form an oxide film on the surface of the surface-expanding layer. In the chemical conversion treatment of the cathode foil, chlorine attached during the AC etching treatment was removed with an aqueous phosphoric acid solution, and then a voltage of 3 V was applied in an aqueous solution of ammonium dihydrogen phosphate to form an oxide film with a withstand voltage of 3 V.

[0051] The anode foil is a strip-shaped aluminum foil. This anode foil is subjected to a direct current etching process to form a surface expansion layer consisting of tunnel-shaped etching pits on both sides of the foil. A pseudo-boehmite layer of a different weight depending on the embodiment is formed on the anode foil on which this surface expansion layer is formed. This pseudo-boehmite layer is formed by chemical pretreatment. In the chemical pretreatment, the anode foil on which the surface expansion layer is formed is immersed in boiled pure water.

[0052] After the pseudo-boehmite layer was formed, the anode foil was immersed in an aqueous phosphoric acid solution for a short time to dissolve the pseudo-boehmite layer from the surface. Next, as a chemical conversion treatment, the anode foil was immersed in ammonium borate and a chemical conversion voltage was applied. This chemical conversion pretreatment, dissolution of the pseudo-boehmite layer with an aqueous phosphoric acid solution, and chemical conversion treatment were repeated multiple times. Anode foils having pseudo-boehmite layers of various weights were produced by comparing the initial weight after the pseudo-boehmite layer was first formed and the weight after each cycle.

[0053] Table 1 below shows the weight of the pseudo-boehmite layer for various anode foils. (Table 1) TIFF2025059293000005.tif78160

[0054] Aluminum tab-shaped lead-out terminals were ultrasonically connected to the anode foil and cathode foil. Moving on to the element formation process, a separator was sandwiched between the anode foil and cathode foil and rolled up to form a capacitor element. A kraft separator was sandwiched between the foil and rolled up to form a capacitor element. This capacitor element was cylindrical with a diameter of 10 mm and a height of 25 mm.

[0055] Moving on to the impregnation process, the capacitor elements were impregnated with electrolyte solutions containing different concentrations of boric acid, as shown in Table 2 below. (Table 2) TIFF2025059293000006.tif66160

[0056] In addition, in each electrolyte, the additives are phosphoric acid compounds and nitro compounds, and the polymer component is silicone oil. After the electrolyte is impregnated into the capacitor element, it is housed in a cylindrical case with a pressure valve formed at the bottom, and the opening of the cylindrical case is sealed with a sealing body. A voltage is applied to the electrolytic capacitor, and aging is performed. In this way, 24 types of electrolytic capacitors of Examples 1 to 12, Comparative Examples 1 to 4, and Reference Examples 1 to 8 having each combination of the six types of pseudo-boehmite layers and four types of electrolytes shown in Tables 1 and 2 were produced.

[0057] (Cathode foil deterioration) The electrolytic capacitors of Examples 1 to 12, Comparative Examples 1 to 4, and Reference Examples 1 to 8 were left unloaded for 170 hours in a high-temperature environment at 150°C. These electrolytic capacitors were disassembled, the cathode foils were washed with water, and the transition of the cathode foil potential (E vs. Pt) was measured. Figures 1 and 2 are graphs showing the transition of the potential over a period of 5 minutes from the steady state through the start of measurement. The measurement was started 1 minute after the steady state.

[0058] As shown in Figures 1 and 2, the potential of the cathode foil shown in several graphs rises sharply from the start of measurement, becoming at least 0.5 V more noble in 10 seconds with platinum as the reference electrode. On the other hand, the potential of the cathode foil shown in several other graphs rises slowly from the start of measurement, and does not leave the noble state in 10 seconds with platinum as the reference electrode. The difference between these graphs indicates the state of the oxide film on the cathode foil. When re-chemical formation is working to repair the oxide film on the cathode foil, the potential of the cathode foil becomes low. In other words, when the oxide film on the cathode foil is dissolved, the potential of the cathode foil becomes low.

[0059] That is, if the potential rises sharply from the start of measurement and is at least 0.5 V more noble in 10 seconds using platinum as the reference electrode, dissolution of the oxide film formed on the cathode foil is suppressed, and hydrogen gas is unlikely to be generated. On the other hand, if the potential rises slowly from the start of measurement and does not reach 0.5 V more noble in 10 seconds using platinum as the reference electrode, the oxide film formed on the cathode foil is dissolved, and hydrogen gas is likely to be generated.

[0060] Therefore, for the electrolytic capacitors of Examples 1 to 12, Comparative Examples 1 to 4, and Reference Examples 1 to 8, the measurement was started one minute after the steady state, and the potential of the cathode foil 10 seconds after the start of the measurement is shown in Table 3 below.

[0061] (Table 3) TIFF2025059293000007.tif74165

[0062] As shown in Table 3 above, the electrolytic capacitors of Reference Examples 1 to 8 had a weight of 1.00 mg cm-2 The electrolytic capacitors of Comparative Examples 1 to 4 have a pseudo-boehmite layer with a weight of 1.00 mg cm -2 The electrolytic capacitors of Examples 1 to 12 have the above pseudo-boehmite layer and an electrolyte with a boric acid concentration of 11 wt%. -2 The present invention has the pseudo-boehmite layer and an electrolyte having a boric acid concentration of 9 wt % or less.

[0063] Based on Table 3, the relationship between the potential and the weight of the pseudo-boehmite layer when an electrolyte with a boric acid concentration of 11 wt% is used is shown in Figure 3. As shown in Table 3 and Figure 3, when the weight of the pseudo-boehmite layer is 1.0 mg cm -2 The cathode foils obtained from the electrolytic capacitors of Reference Examples 1 and 2, in which the weight of the pseudo-boehmite layer is less than 1.0 mg cm, have a potential of 0.5 V or more on the noble side with respect to platinum as the reference electrode. -2 When the temperature is less than 1000° C., it can be confirmed that dissolution of the oxide film on the cathode foil is suppressed.

[0064] On the other hand, as shown in Table 3 and Fig. 3, when the weight of the pseudo-boehmite layer was 1.0 mg cm -2 The cathode foils obtained from the electrolytic capacitors of Comparative Examples 1 to 4 have a potential of −0.5 V or less relative to the platinum reference electrode. -2 If this is the case or more, it can be confirmed that dissolution of the oxide film on the cathode foil is progressing.

[0065] Next, based on Table 3, the relationship between the boric acid concentration and the potential of the cathode foil is shown in Figure 4. As shown in Table 3 and Figure 4, when the weight of the pseudo-boehmite layer is 1.0 mg cm -2 Even if the concentration of boric acid in the electrolyte is 9 wt% or less, the cathode foil has a potential of 0.5 V or more on the noble side with respect to platinum as the reference electrode. Therefore, if the weight of the pseudo-boehmite layer is 1.0 mg cm -2 If this is the case or more, it can be confirmed that dissolution of the oxide film on the cathode foil is suppressed.

[0066] Therefore, 1.0 mg cm -2By leaving a pseudo-boehmite layer of this weight or more and realizing a high withstand voltage of 550 V or more, while keeping the boric acid concentration of the electrolyte at 9 wt% or less, the generation of hydrogen gas is suppressed, thereby extending the life of the electrolytic capacitor.

[0067] (Mannitol ratio) An electrolytic capacitor of Comparative Example 5 was produced by changing the amount of mannite in the electrolyte. Except for the difference in the amount of mannite, the electrolytic capacitor of Comparative Example 5 was produced by the same method and under the same conditions as the electrolytic capacitor of Example 2, and the weight of the pseudo-boehmite layer was 1.53 mg cm -2 and have the same composition, including the boric acid concentration of 9 wt %.

[0068] The composition of the electrolyte of Comparative Example 5 is as shown in electrolyte composition 5 in Table 4 below. Electrolyte composition 2 is the composition of the electrolyte used in the electrolytic capacitor of Example 2. As shown in Table 4 below, the weight ratio of mannitol to boric acid in Example 2 is 0.7, while the weight ratio of mannitol to boric acid in Comparative Example 5 is 0.4.

[0069] (Table 4) TIFF2025059293000008.tif59161

[0070] The electrolytic capacitors of Example 2 and Comparative Example 5 were left unloaded for 170 hours in a high-temperature environment at 150°C. These electrolytic capacitors were disassembled, the cathode foils were washed with water, and the transition of the cathode foil potential (E vs. Pt) was measured. The measurement was started one minute after the steady state, and the potential of the cathode foil 10 seconds after the start of the measurement is shown in Table 5 below.

[0071] (Table 5) TIFF2025059293000009.tif20161

[0072] Based on Table 5, the relationship between the weight ratio of mannitol to boric acid and the potential of the cathode foil is shown in Figure 5. As shown in Table 5 and Figure 5, when the weight ratio of mannitol to boric acid is 0.7 or more, the potential of the cathode foil 10 seconds after the start of measurement becomes high, and it can be confirmed that the deterioration of the oxide film on the cathode foil is suppressed.

[0073] In this example, the deterioration of the cathode foil (dissolution of the oxide film) was verified by measuring the transition of the potential of the cathode foil used in the electrolytic capacitor after it was left unloaded in a high-temperature environment. When using a cathode foil on which an oxide film is not intentionally formed, it is possible to verify the deterioration of the cathode foil by, for example, measuring the amount of hydrogen gas generated by the electrolytic capacitor after it is left unloaded in a high-temperature environment.

Claims

1. An electrolytic capacitor including an anode foil made of a valve metal, a cathode body, and an electrolyte, The anode foil is a dielectric film formed on a surface layer of the anode foil; formed on the dielectric film, 2 The pseudo-boehmite layer and having The electrolyte contains boric acid in an amount of 9 wt % or less based on the total amount of the electrolyte; An electrolytic capacitor characterized by:

2. The electrolyte contains a solvent for a glycol compound; 2. The electrolytic capacitor according to claim 1 .

3. The weight of the pseudo-boehmite layer is 1.3 mg / cm 2 That is all, 3. The electrolytic capacitor according to claim 1 or 2,

4. The boric acid contains boric acid in an amount of 8.3 wt % or less based on the total amount of the electrolyte; 3. The electrolytic capacitor according to claim 1 or 2,

5. The electrolyte contains mannitol, The weight ratio of the boric acid (A) and the mannitol (B) in the electrolyte solution is A:B=1:0.7 or more; 3. The electrolytic capacitor according to claim 1 or 2,

6. a pre-chemical conversion step of forming a pseudo-boehmite layer on an anode foil based on a valve metal; The pseudo-boehmite layer is 1.0 mg / cm 2 a chemical conversion step of forming the dielectric film while leaving the above; an element forming step of forming a capacitor element in which the anode foil that has been subjected to the chemical conversion step and a cathode body are opposed to each other with a separator interposed therebetween; an impregnation step of impregnating the capacitor element with an electrolyte solution having a boric acid concentration of 9 wt % or less; containing, A method for manufacturing an electrolytic capacitor comprising the steps of:

Citation Information

Patent Citations

  • Electrolytic capacitor cathode foil and method of manufacturing the same

    JP2010219083A